2021
DOI: 10.1038/s41416-021-01560-1
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of Schlafen11 (SLFN11) to predict the outcomes to therapies affecting the DNA damage response

Abstract: Background The absence of the putative DNA/RNA helicase Schlafen11 (SLFN11) is thought to cause resistance to DNA-damaging agents (DDAs) and PARP inhibitors. Methods We developed and validated a clinically applicable SLFN11 immunohistochemistry assay and retrospectively correlated SLFN11 tumour levels to patient outcome to the standard of care therapies and olaparib maintenance. Results High SLFN11 associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…This data suggests that there can be additional dependencies for synergism, which is likely related to each cell line’s repertoire of mutational signatures. As supported by our perturbation screen and previous studies, decreased SLFN11 expression is responsible for drug resistance to DNA-damaging agents (33). Based on the publicly available data set (merav.wi.mit.edu/) (34), SLFN11 expression is significantly lower in SNU16 cells compared to SNU5 cells, which may be the cause of the breached correlation between ABCG2 expression and synergism (Figure S7F).…”
Section: Discussionsupporting
confidence: 83%
“…This data suggests that there can be additional dependencies for synergism, which is likely related to each cell line’s repertoire of mutational signatures. As supported by our perturbation screen and previous studies, decreased SLFN11 expression is responsible for drug resistance to DNA-damaging agents (33). Based on the publicly available data set (merav.wi.mit.edu/) (34), SLFN11 expression is significantly lower in SNU16 cells compared to SNU5 cells, which may be the cause of the breached correlation between ABCG2 expression and synergism (Figure S7F).…”
Section: Discussionsupporting
confidence: 83%
“…While the mechanisms of SLFN11‐mediated cell killing are not fully understood, the importance of SLFN11 in drug sensitivity is validated in various settings 47 , 48 , 49 , 50 (see recent reviews 38 , 51 ). Patient data are also accumulating with a broad type of cancers including breast cancer, 50 , 52 ovarian cancer, 53 gastric cancer, 54 bladder cancer, 55 small cell lung cancer, 56 esophageal cancer, 57 and prostate cancer. 58 Notably, most of these data have been obtained without considering the presence or absence of BRCA or HR deficiency.…”
Section: Slfn11 Is a Common Sensitizer To Platinum Derivat...mentioning
confidence: 99%
“…Recently, the group of AstraZeneca examined the effect of SLFN11 on olaparib sensitivity. 56 They first showed that patients with high‐SLFN11 tumors had significantly longer overall survival when treated with first‐line platinum and etoposide in small cell lung cancer. Although the role of SLFN11 was uncertain in their cohort of high‐grade serous ovarian cancers treated with paclitaxel‐platinum, they found that high levels of SLFN11 were associated with improved clinical outcomes with olaparib treatment.…”
Section: Does Slfn11 Need Brca ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing model is that SLFN11 is recruited to replication forks under replication stress where the replicative helicases and polymerases are uncoupled, which causes the formation of extended RPA-coated ssDNA that recruits SLFN11 to irreversibly arrests replication. SLFN11 also confers hypersensitivity to PARPis in pre-clinical models [9,29,30], and a recent clinical study analyzing the effects of SLFN11 on olaparib sensitivity in patients with ovarian cancer showed that high SLFN11 expression is associated with improved clinical outcome [31]. Notably, subgroup analyses revealed that only patients with both BRCA mutations and high SLFN11 expression bene ted signi cantly from olaparib treatment.…”
Section: Introductionmentioning
confidence: 99%